2009
DOI: 10.17221/1111-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cheese Type and Maturation Time on the Early Maillard Reaction in Cheese

Abstract: Formation and degradation of Amadori products (APs) originating from the early Maillard reaction during maturation of three different commercial cheeses, namely Cheddar, Emmentaler and Gouda, was investigated. APs were analysed as the corresponding n-(furoylmethyl) amino acids formed after acid hydrolysis. The contents of furosine, which is a hallmark for Amadori products resulting from derivatisation of lysine at the ε-amino group (ε-APs), ranged from 4 to 20 mg/100 g protein, corresponding to 33 to 159 µmol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Especially primary amino groups are capable of the reaction with residual lactose and the monosaccharides galactose and glucose. The content of 6 of the Gouda cheeses (Figure ) was in line with the findings of Schwietzke et al . and exceeded the concentrations of the Amadori product within the acid curd cheese (Figure ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Especially primary amino groups are capable of the reaction with residual lactose and the monosaccharides galactose and glucose. The content of 6 of the Gouda cheeses (Figure ) was in line with the findings of Schwietzke et al . and exceeded the concentrations of the Amadori product within the acid curd cheese (Figure ).…”
Section: Discussionsupporting
confidence: 90%
“…Especially primary amino groups are capable of the reaction with residual lactose and the monosaccharides galactose and glucose. The content of 6 of the Gouda cheeses (Figure 7) was in line with the findings of Schwietzke et al 15 and exceeded the concentrations of the Amadori product within the acid curd cheese (Figure 6). The reasons can be related to different processing conditions such as enhanced whey drainage and heat treatment or to differences in the composition of the raw material.…”
Section: ■ Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Manchego (Corzo, Villamiel, Arias, Jiménez-Pérez, & Morales, 2000), Cheddar, Gouda and Emmental (Schwietzke, Schwarzenbolz, & Henle, 2009), Harzer and Gouda cheeses (Spanneberg, Salzwedel, & Glomb, 2012) have been reported that the Maillard reaction proceeded along with cheese maturation of these cheeses. These studies measured Maillard reaction products in young and matured cheese using high performance liquid chromatography analysis.…”
Section: Vip and Sr Scores Of The Plsr Model Plotted Using Ff Contourmentioning
confidence: 97%